Understanding Public Perception of Waste Management in Western Balkans using Tweets and News Reports Analysis - Gjorshoska, Ivana; Madjar, Angela; Dedinec Kanevche, Aleksandra; Prodanova, Jana (My University, 2022)
The rapid urbanization and economic growth greatly contribute to the increasing amount of produced solid waste worldwide. As part of their pro-European policies, many countries from the Western Balkans have started to accept and apply the EU Waste Management Law in their legal systems as well as in practice in order to create adequate waste management schemes. The aim of this paper is to analyze the public response regarding waste management regulations and practices using Twitter and News reports data analysis within a period of four months, between November 1st, 2021 and February 28th, 2022. Sentiment analysis and Dynamic Topic Modeling were used to assess the public attitude in both news reports and Twitter responses, in addition to bigrams similarity using soft cosine measure to determine the semantic correlation between the two sources. The results suggest that there is a predominantly negative attitudes towards waste practices in both media outlets. Additionally, there is a strong semantic correlation between the discussed topics in news reports and on social media, leading to the conclusion that news outlets play a major role in promoting pro-environmental behavior in the general public in Western Balkans.
Keywords: waste management, Western Balkans, social media, twitter analysis, news reports, sentiment analysis, dynamic topic modeling, semantic similarity